Asian Americans and Internalized Racial Oppression: Identified, Reproduced, and Dismantled. Issue 1 (January 2018) - Trieu, Monica M.; Lee, Hana C.
Internalized racial oppression among Asian Americans is currently an understudied topic in the social sciences. In this article, the authors draw from 52 in-depth interviews with 1.5- and 2nd-generation Asian Americans to examine this phenomenon. Although previous studies have examined individuals who engage in, and reproduce, internalized racial oppression from static lenses, the present research shows that individuals can (and do) shift out of perceptions and behaviors that perpetuate internalized racism. This research pinpoints the factors that assist in this fluid process. The findings show that the factors are centrally framed around the theme of critical exposure. In particular, it is the critical exposure to ethnic and racial history, ethnic organizations, and coethnic ties that ultimately leads to the emergence of an empowering critical consciousness, which is the necessary key in diverting Asian Americans away from behaviors that perpetuate internalized racial oppression.